Bronchodilator response assessment through impulse oscillometry system and spirometry in children and adolescents with cystic fibrosis - Tayná Castilho; José Dirceu Ribeiro; Renata Maba Gonçalves Wamosy; Juliana Cardoso; Gabriela Castilhos Ducati; Camila Isabel Santos Schivinski (Revista Paulista de Pediatria, 2024)
ABSTRACT Objective: To investigate the effect of bronchodilator on the respiratory mechanics and pulmonary function of children and adolescents with cystic fibrosis. Methods: Cross-sectional study on clinically stable children and adolescents with cystic fibrosis aged from six to 15 years. Participants underwent impulse oscillometry and spirometry evaluations before and 15 minutes after bronchodilator inhalation. The Kolmogorov-Smirnov test was applied to verify the sample distribution, and the Student's t-test and Wilcoxon test were used to compare the data before and after bronchodilator inhalation. Results: The study included 54 individuals with a mean age of 9.7±2.8 years. The analysis showed a statistically significant improvement in impulse oscillometry and spirometry parameters after bronchodilator inhalation. However, according to the American Thoracic Society (ATS) and European Respiratory Society (ERS) recommendations (2020 and 2021), this improvement was not sufficient to classify it as a bronchodilator response. Conclusions: The use of bronchodilator medication improved respiratory mechanics and pulmonary function parameters of children and adolescents with cystic fibrosis; however, most patients did not show bronchodilator response according to ATS/ERS recommendations.